Algorithms used in heterogeneous dose calculations show systematic differences as measured with the Radiological Physics Center’s anthropomorphic thorax phantom used for RTOG credentialing - Kry, Stephen F. (2013)
PURPOSE: To determine the impact of treatment planning algorithm on the accuracy of heterogeneous dose calculations in the Radiological Physics Center (RPC) thorax phantom. METHODS AND MATERIALS: We retrospectively analyzed the results of 304 irradiations of the RPC thorax phantom at 221 different institutions as part of credentialing for RTOG clinical trials; the irradiations were all done using 6-MV beams. Treatment plans included those for intensity-modulated radiation therapy (IMRT) as well as 3D conformal therapy (3D CRT). Heterogeneous plans were developed using Monte Carlo (MC), convolution/superposition (CS) and the anisotropic analytic algorithm (AAA), as well as pencil beam (PB) algorithms. For each plan and delivery, the absolute dose measured in the center of a lung target was compared to the calculated dose, as was the planar dose in 3 orthogonal planes. The difference between measured and calculated dose was examined as a function of planning algorithm as well as use of IMRT. RESULTS: PB algorithms overestimated the dose delivered to the center of the target by 4.9% on average. Surprisingly, CS algorithms and AAA also showed a systematic overestimation of the dose to the center of the target, by 3.7% on average. In contrast, the MC algorithm dose calculations agreed with measurement within 0.6% on average. There was no difference observed between IMRT and 3D CRT calculation accuracy. CONCLUSION: Unexpectedly, advanced treatment planning systems (those using CS and AAA algorithms) overestimated the dose that was delivered to the lung target. This issue requires attention in terms of heterogeneity calculations and potentially in terms of clinical practice.